Computationally-inspired discovery of an unsymmetrical porous organic cage. Issue 47 (26th November 2018) - Berardo, Enrico; Greenaway, Rebecca L.; Turcani, Lukas; Alston, Ben M.; Bennison, Michael J.; Miklitz, Marcin; Clowes, Rob; Briggs, Michael E.; Cooper, Andrew I.; Jelfs, Kim E.
Abstract : Computationally inspired and rationalised discovery of a completely unsymmetrical organic cage, which was both porous and highly soluble. Abstract : A completely unsymmetrical porous organic cage was synthesised from a C 2v symmetrical building block that was identified by a computational screen. The cage was formed through a 12-fold imine condensation of a tritopic C 2v symmetric trialdehyde with a ditopic C 2 symmetric diamine in a [4 + 6] reaction. The cage was rigid and microporous, as predicted by the simulations, with an apparent Brunauer–Emmett–Teller surface area of 578 m 2 g −1 . The reduced symmetry of the tritopic building block relative to its topicity meant there were 36 possible structural isomers of the cage. Experimental characterisation suggests a single isomer with 12 unique imine environments, but techniques such as NMR could not conclusively identify the isomer. Computational structural and electronic analysis of the possible isomers was used to identify the most likely candidates, and hence to construct a 3-dimensional model of the amorphous solid. The rational design of unsymmetrical cages using building blocks with reduced symmetry offers new possibilities in controlling the degree of crystallinity, porosity, and solubility, of self-assembled materials.